Motor speech impairment predicts expressive language in minimally verbal, but not low verbal, individuals with autism spectrum disorder. (June 2019) - Chenausky, Karen; Brignell, Amanda; Morgan, Angela; Tager-Flusberg, Helen
Background and aims: Developmental motor speech impairment has been suspected, but rarely systematically examined, in low- and minimally verbal individuals with autism spectrum disorder. We aimed to investigate the extent of motor speech impairment in this population and its relation to number of different words produced during a semi-structured language sample. Methods: Videos of 54 low-verbal and minimally verbal individuals (ages 4;4–18;10) performing portions of a speech praxis test were coded for signs of motor speech impairment (e.g., childhood apraxia of speech). Age, autism spectrum disorder severity, nonspeech oral-motor ability, speech production ability, nonverbal IQ, and receptive vocabulary were compared between groups. Results: Four groups emerged: (1) speech within normal limits ( n = 12), (2) non-childhood apraxia of speech impairment ( n = 16), (3) suspected childhood apraxia of speech ( n = 13), and (4) insufficient speech to rate ( n = 13). Groups differed significantly in nonspeech oral-motor ability, speech production ability, nonverbal IQ, and receptive vocabulary. Overall, only speech production ability and receptive vocabulary accounted for significant variance in number of different words. Receptive vocabulary significantly predicted number of different words only in Groups 1 and 2, while speech production ability significantly predicted number of different words only in Groups 3 and 4. Conclusions and implications: If replicated, our findings have important implications for developing much-needed spoken language interventions in minimally verbal individuals with autism spectrum disorder.